Pengaruh Religiostik, EWOM, Brand Image dan Attitude terhadap Purchase Intention - Lily Purwianti (LPPM Universitas BSI, 2021)
ABSTRACTThe growth of the cosmetics industry in Indonesia is very encouraging for competition between cosmetic manufacturers in Indonesia. The cosmetic competition from South Korea increases the competition to be very complex. Indonesia, which is most important for Islam, poses a different challenge for cosmetic producers so that the religiosity factor must be considered. With the spread of the internet around the world, interpersonal communication has been reshaped from traditional face-to-face communication to a more virtual way of communication called electronic word of mouth (E-WOM), where consumers have a great opportunity to share information about their consumption experiences and for investment advice on products and brands using social networking platforms and consumer review sites. This study aims to study whether religiosity, EWOM, brand image, and attitudes influence purchase intention. The research sample is the people of Batam city who see cosmetics from South Korea. The number of samples in this study was 320 respondents with a purposive sample technique. Structural Equation Modeling (SEM) based on Partial Least Square (PLS) was used in this study. The results of this study are that religiosity affects attitudes and purchase intentions, EWOM affects attitudes and purchase intentions, and attitudes that affect purchase intentions. Everything else from this study is that brand image does not affect purchase attitudes and intentions. Keywords: religiostic, EWOM, brand image, attitude, purchase intention